Building an Ethical AI Framework for Governments and Corporations (Journal of responsible AI & ethics, 2026)
Artificial Intelligence has become one of the most transformative technologies shaping modern governance and corporate decision-making. Governments and corporations increasingly rely on AI systems to automate processes, analyze large datasets, optimize public services, and improve operational efficiency. However, the rapid adoption of AI technologies has also raised serious ethical concerns related to transparency, fairness, accountability, data privacy, and algorithmic bias. Without appropriate ethical frameworks, AI systems may unintentionally reinforce social inequalities, violate individual rights, or create governance challenges. This paper explores the need for a comprehensive ethical AI framework designed specifically for governments and corporations. The research analyzes how ethical principles such as transparency, accountability, fairness, and human oversight can be integrated into AI systems. The study examines policy initiatives, corporate governance practices, and ethical guidelines developed by international organizations to understand how AI governance can be implemented effectively. Using mixed-method research involving policy analysis, case studies, and stakeholder surveys, the study evaluates the challenges organizations face when implementing ethical AI frameworks.